EFL Students’ Perceptions in Vocabulary Mastery through Instagram - Nengsih, Mardela; Azhar, Fadly; Novitri, Novitri (Journal of Educational Sciences, 2025)
The background of this study emphasizes Instagram as a digital platform where EFL students are able to use it in order to enrich their vocabulary mastery. Due to that situation, this research aims to find out the EFL students’ perceptions in vocabulary mastery through Instagram. This study applied mixed method with explanatory sequential design. In collecting the data, the researcher used close-ended questionnaire and semi-structured interview. This research involved 75 EFL students at English Department, FKIP, Universitas Riau class 2022. Among those EFL students, 6 students were chosen to be the interviewees. The finding showed the average mean score of all indicators was 3.65 (medium level). It can be inferred that the participants presented positive perceptions about vocabulary mastery on Instagram. They seemed to be using Instagram often and felt the content of Instagram is interesting which made them feel more motivated to learn vocabulary. With the help of Instagram, EFL students comprehend more about pronunciation, verbs, prepositions, and hyponyms because Instagram provides many contents about them.